1998
DOI: 10.1021/jm9803572
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Salicylanilides as Inhibitors of Two-Component Regulatory Systems in Bacteria

Abstract: A new class of inhibitors of the two-component regulatory systems (TCS) of bacteria was discovered based on the salicylanilide screening hits, closantel (1) and tetrachlorosalicylanilide (9). A systematic SAR study versus a model TCS, KinA/Spo0F, demonstrated the importance of electron-attracting substituents in the salicyloyl ring and hydrophobic groups in the anilide moiety for optimal activity. In addition, derivatives 8 and 16, containing the 2, 3-dihydroxybenzanilide structural motif, were potent inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 20 publications
6
81
0
2
Order By: Relevance
“…We observed that, in agreement with recent reports by Rajamuthiah et al (13), niclosamide showed strong antimicrobial activity against planktonic S. aureus with an IC 50 of 1.2 M. Furthermore, closantel, a homologue of niclosamide, also showed significant antimicrobial activity against planktonic S. aureus with an IC 50 below the lowest concentration tested (0.6 M), in agreement with the findings of Macielag et al (14).…”
Section: Resultssupporting
confidence: 93%
“…We observed that, in agreement with recent reports by Rajamuthiah et al (13), niclosamide showed strong antimicrobial activity against planktonic S. aureus with an IC 50 of 1.2 M. Furthermore, closantel, a homologue of niclosamide, also showed significant antimicrobial activity against planktonic S. aureus with an IC 50 below the lowest concentration tested (0.6 M), in agreement with the findings of Macielag et al (14).…”
Section: Resultssupporting
confidence: 93%
“…Indeed, compounds that inhibit signal transduction through these systems have been shown to be effective even against multi-drug-resistant pathogens, including methicillin-resistant S. aureus and vancomycin-resistant Enterococcus faecium (2,20). The data presented here suggest that manipulation of SrrA-SrrB in S. aureus may suppress production of exotoxins.…”
Section: Vol 183 2001mentioning
confidence: 78%
“…Histidine kinase is the focus for the specific inhibition of two component signal transduction system in mycobacteria (95)(96)(97)(98). Based on this signal transduction system, a series of antimycobacterial salicylanilides and related compounds have been reported (99)(100)(101)(102). Inhibition of this type of regulation has been involved in the virulence of M. tuberculosis in mice (103).…”
Section: 24-benzothiadiazinesmentioning
confidence: 99%